Influence of the Atmospheric Mass on the High Energy Cosmic Ray Muons during a Solar Cycle - A. H. Maghrabi; R. N. Alotaibi; M. M. Almutayri; M. S. Garawi (Advances in Astronomy)
The rate of the detected cosmic ray muons depends on the atmospheric mass, height of pion production level, and temperature. Corrections for the changes in these parameters are importance to know the properties of the primary cosmic rays. In this paper, the effect of atmospheric mass, represented here by the atmospheric pressure, on the cosmic ray was studied using data from the KACST muon detector during the 2002–2012 period. The analysis was conducted by calculating the barometric coefficient (α) using regression analysis between the two parameters. The variation of α over different time scales was investigated. The results revealed a seasonal cycle of α with a maximum in September and a minimum in March. Data from Adelaide muon detector were used, and different monthly variation was found. The barometric coefficient displays considerable variability at the interannual scale. Study of the annual variations of α indicated cyclic variation with maximums between 2008 and 2009 and minimums between 2002 and 2003. This variable tendency is found to be anticorrelated with the solar activity, represented by the sunspot number. This finding was compared with the annual trend of α for the Adelaide muon detector for the same period of time, and a similar trend was found.